Management of Pondok Pesantren Facilities and Infrastructure From the Perspective of Child Rights Protection - Yulia Luthfiyani Azizah; Zulfida Aulia Fatimah; Novi Fitriana; Zainal Arifin Ahmad (Vifada Journal of Education, 2026)
This study examines the management of pondok pesantren facilities and infrastructure from a child rights perspective, highlighting the gap between building safety standards and on-the-ground management practices. The study focuses on how the management of pondok pesantren educational facilities relates to the fulfillment of students' rights to safety, health, comfort, and a decent learning environment. The study uses a library method with a content analysis approach, drawing on primary data from regulations on education, pondok pesantren, and child protection, as well as secondary data from scientific journals, official government reports, and other supporting documents. The analysis used the POAC (Planning, Organizing, Actuating, and Controlling) management function to examine the management of pondok pesantren facilities and infrastructure from a child protection perspective. The study's results indicate a gap between regulations and the implementation of facility management. Persetujuan Bangunan Gedung (PBG) and Sertifikat Laik Fungsi (SLF), weak supervision, financial constraints, and a culture of self-help development are the main factors hindering compliance with safety standards in pondok pesantren. This condition affects the suboptimal fulfillment of children's rights to a safe and decent educational environment. This study also highlights that the concept of Pesantren Ramah Anak can serve as a model for managing facilities and infrastructure that are more oriented towards the protection and welfare of students, by prioritizing the safety, comfort, and rights of children in the management of pondok pesantren educational facilities.